2007
DOI: 10.1093/jac/dkm398
|View full text |Cite
|
Sign up to set email alerts
|

Besifloxacin, a novel fluoroquinolone antimicrobial agent, exhibits potent inhibition of pro-inflammatory cytokines in human THP-1 monocytes

Abstract: Besifloxacin acts as an anti-inflammatory agent in monocytes in vitro; this attribute may enhance its efficacy in ocular infections with an inflammatory component and warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…In addition, anti-inflammatory effects of quinolones, such as moxifloxacin (Araujo et al, 2002), gatifloxacin (Takeyama et al, 2007), ciprofloxacin (Kaji et al, 2008), and besifloxacin (Zhang and Ward, 2008), have also been reported. In Table 1, we list several reports about inhibitory effects of antibiotic on IL-8 production induced by stimuli in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, anti-inflammatory effects of quinolones, such as moxifloxacin (Araujo et al, 2002), gatifloxacin (Takeyama et al, 2007), ciprofloxacin (Kaji et al, 2008), and besifloxacin (Zhang and Ward, 2008), have also been reported. In Table 1, we list several reports about inhibitory effects of antibiotic on IL-8 production induced by stimuli in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…It is a sterile solution containing the equivalent of 6 mg/mL of besifloxacin and 0.01% benzalkonium chloride (BAK). [13][14][15] Currently, besifloxacin is approved in the United States and Canada for treatment of bacterial conjunctivitis due to susceptible isolates of Haemophilus influenzae, Streptococcus pneumoniae and other streptococci, Moraxella lacunata, and common species of Corynebacterium sp., as well as susceptible species of Staphylococcus aureus and Coagulase-negative staphylococci. 16 Similar to current fluoroquinolones, besifloxacin inhibits bacterial enzymes DNA gyrase and topoisomerase IV, which are essential for DNA repair, replication, transcription, and partitioning.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when MRSA is resistant to gatifl oxacin or moxifl oxacin, that resistance appears to be reliably carried over to besifl oxacin as well. [14][15][16][17][18] Unlike systemic antibiotics, topical antibiotics are delivered to the eye suspended in a vehicle of preservatives, osmotic agents, and buffers. These excipients are delivered concurrently to the site of infection along with the antibiotic.…”
Section: Discussionmentioning
confidence: 99%